Dementia family caregiving experience among Asian American older adults - Choi, JiWon; Park, Van Ta; Vuong, Quyen; Cheng, Joyce; Mukherjea, Arnab; Tsoh, Janice Y (Alzheimer's & dementia, 2021)
Asian Americans are almost twice more likely to assume caregiving roles for their family than the general population. More Asian American dementia caregivers (DCGs) find their role highly stressful than African American or Hispanic DCGs. Research exploring the challenges and coping strategies for Asian American DCGs is limited. This qualitative study, entitled the SHARE (Share History, Activity, Resilience, and Experience) Project, was conducted to explore the challenges and coping strategies among Asian American DCGs. Focus groups and individual interviews were conducted with 29 Asian Americans in the Bay Area between July-December 2020. The inclusion criteria were: 1) age ≥ 50 years 2) self-identified as Chinese, Indian, Korean, or Vietnamese American; and 3) provide ≥ 5 hours of care/week currently or in the past for dementia care recipient. Participants were recruited through local community service agencies, the community advisory board of this study, online networks, and word of mouth. Interviews that were conducted in Cantonese, Korean, and Vietnamese were transcribed and translated in . Ethnically/linguistically matched moderators facilitated eight focus groups (six via zoom video and two via WeChat video; three in English, two in Cantonese, one in Korean, and two in Vietnamese) and two individual interviews via telephone (one in English and one in Vietnamese) using the structured interview guide. About two thirds were current DCGs. Participants reported care recipient's behavior-related challenges (e.g., arguing, forgetfulness, wandering) and dementia-related challenges (e.g., uncertainty, helplessness, duty for 24/7). Across all focus groups, filial piety, love, or responsibility as a family were the main source of enduring. Participants reported exercise, distraction, positive thinking, and having time alone as coping strategies. Having multigenerational families or a care team approach for care recipients appeared to decrease caregiving burden. Not feeling guilty or shame about one's limitation and using informal/formal support in a timely manner may also help. Some DCGs also expressed a need for social networking with other DCGs for information and emotional support. Needs for affordable and/or culturally appropriate formal care services were found. Education and training for DCGs given by former DCGs may be useful to disseminate coping strategies.